Research on new kind of parallel packet switch based on CICQ - REN Tao; LAN Ju-long; HU Hong-chao; CHENG Dong-nian (Tongxin xuebao)
A distributed CICQ based DiffServ supporting parallel packet switch（CDPPS） was proposed.By using multiple low speed switches to construct parallel packet switch,CDPPS made it possible to construct DiffServ supporting scheduling scheme in high speed environment.Because CICQ could be used as central plane without any modification,CDPPS increased the efficiency of existing resources.As a result of using distributed scheduling algorithm,CDPPS eliminates the communication overhead,and reduces the hardware implementation complexity.Theoretic analysis and simulation results show that CDPPS can provide satisfying QoS for different traffic classes.